Single Crystal SiC Capacitive pressure sensor design and analysis using MEMS Pro L-Edit and Samcef Field & Oofelie software - Ruhaizi Mohd Hatta (Universiti Malaysia Perlis, 2008)
Access is limited to UniMAP community.